Tribes we need you to lead us - Godin, Seth. (New York Portfolio, 2008)
A tribe is any group of people, large or small, who are connected to one another, a leader, and an idea. For millions of years, humans have been seeking out tribes, be they religious, ethnic, economic, political, or even musical (think of the Deadheads). It?s our nature.
Keywords: Leadership